Incorporating strawberry leaf extract from waste biomass in prototype topical gel and cream formulations - Karla Salas-Arias; Fabián Villalta-Romero; Randall Chacón-Cerdas; David Hidalgo-Paniagua; Laura Calvo-Castro (Tecnología en Marcha)
Berry fruits are an important source of polyphenols with beneficial antioxidant properties for human health. However, higher bioactive phytochemical content has been reported in berry leaves, which are usually discarded or underutilized. In this study, a hydroalcoholic extract with relevant polyphenol content obtained from strawberry leaves (Fragaria x ananassa cv. Festival), an agro-industrial waste material, was incorporated in two commercial topical formulations (aqueous gel and oil/water cream), in three concentrations of active ingredient (0.02, 0.1 and 1% strawberry leaf extract). The physicochemical properties of the formulations were monitored for 45 days at different temperatures. Particle size and stability analysis showed that the cream based formulations were the most optimal for the development of a topical prototype with potential bioactive activities.